NILAI-NILAI MORAL DALAM NOVEL AYAHKU BUKAN PEMBOHONG KARYA TERE LIYE DAN IMPLIKASINYATERHADAP PEMBELAJARAN TEKS NOVEL DI SMA - Sukma, Elfira; Hafrison, Mohd. (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
AbstractÂ Study mean to explain the following two things. First, it describes the moral values of the novel My Father, Not a lie by Tere Liye. Second, the behavior shown in the characters. This type of research is qualitative using descriptive methods. The data source in this study is the novel My Father, Not a lie by Tere Liye. The data in this study are in the form of statement sentences, dialogues, and paragraphs. Data collection techniques, namely reading and marking events through the character's speech and the behavior shown by the characters. Second, recording data about moral values found in this novel by looking at the character's speech. Third, inventory data using inventory data tables. The technique of validating the data used a detailed description technique. The research result shows the following matters. First, the moral values in the novel My Father, Not a lie by Tere Liye contain 63 units of events. Second, the behavior shown in the novel My Father, Not a lie by Tere Liye, good morals consists of 53 units of events, while the behavior of bad moral values consists of 10 units of events.Â Kata Kunci: Nilai, Moral, Novel, Implikasi